PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KOMPETENSI TENAGA KESEHATAN DI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - Wahyudiyono, Wahyudiyono; Najib, Khoiri; Suminah, Suminah (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2023)
The purpose of this writing is to examine the effect of education (X1) and training (X2) on the competence of health workers (Y) at PKU Muhammadiyah Yogyakarta Hospital. The writing method uses quantitative methods. The population used is all health workers at PKU Muhammadiyah Yogyakarta Hospital with a probability sampling sample. The distribution of questionnaires was distributed to health workers as many as 57 respondents. Data collection was carried out through a questionnaire that had been tested for validity and reliability. The data analysis technique used is multiple linear regression. The hypothesis is tested using the T test, F test and determination test. The results of data analysis showed that there was a partial effect of the education and training variables as indicated by the results of the t count of education of 13.051 and the result of t count of training of 26.783 which is greater than t table = 2.005 with each having a significance value of 0.000 <0.05. And there is the influence of education and training variables simultaneously where the calculated F result is 366.116 greater than the F table of 3.168 with a significant value of 0.000 <0.05. While the contribution value of the independent variable to the dependent variable is 93.1% and the remaining 6.9% is influenced by other variables not examined in this study.